2022
DOI: 10.3390/vaccines10122163
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Behaviors Regarding Lyme Borreliosis Prevention in the Endemic Area of Northeastern Poland

Abstract: (1) Background: The incidence of Lyme borreliosis (LB) is increasing in Europe. The new LB vaccine is still in clinical development, thus the dissemination of knowledge about the disease is essential. We assessed the knowledge, attitudes and preventive practices (KAP) against tick-borne diseases (TBDs) of people living in the endemic area in northeastern Poland. (2) Methods: We surveyed 406 adults using a 37-item anonymous paper survey. The data were analyzed with regression models. (3) Results: The two most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
3
2
0
Order By: Relevance
“…These findings are in accordance with other studies confirming that women, persons with a high education level and better knowledge and awareness about TBD, were more likely able to prevent tick bites [15,16]. Numerous studies have confirmed that increased risk perceptions positively affect the use of prevention measures [16]. The current study only partially confirmed that high awareness and personal experience influence tick protection behaviours.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings are in accordance with other studies confirming that women, persons with a high education level and better knowledge and awareness about TBD, were more likely able to prevent tick bites [15,16]. Numerous studies have confirmed that increased risk perceptions positively affect the use of prevention measures [16]. The current study only partially confirmed that high awareness and personal experience influence tick protection behaviours.…”
Section: Discussionsupporting
confidence: 92%
“…The use of protective measures was higher among respondents with diagnosed or suspected Lyme borreliosis before participation in the prophylaxis programme. These findings are in accordance with other studies confirming that women, persons with a high education level and better knowledge and awareness about TBD, were more likely able to prevent tick bites [15,16]. Numerous studies have confirmed that increased risk perceptions positively affect the use of prevention measures [16].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations